The girl from Berlin - Balson, Ronald H. (Balson, Ronald H. Liam and Catherine., 2018)
Catherine Lockhart and Liam Taggart investigate a German violin prodigy's handwritten records from Berlin's interwar period to resolve a land dispute between a powerful corporation and a woman facing the loss of her Tuscan hills home.